Relationship between corporate sustainability performance and corporate financial performance: The case of companies from the WIG-ESG Index - Matuszewska-Pierzynka Agnieszka (Economics and Business Review)
The aim of this paper is to identify the effect of corporate sustainability performance (CSP) on corporate financial performance (CFP) among Polish companies in all dimensions of sustainability. The main research hypothesis states that the relationship between CSP and corporate sales performance is positive. The empirical verification of this hypothesis was conducted among 21 companies from the WIG-ESG Index in two periods: 2012–2021 and 2016–2021. The main finding is that sales revenues are positively affected by environmental sustainability performance (years 2012–2021), while governance sustainability performance has a positive impact on the return on sales (years 2016–2021).